Lafoeina longitheca Jaderholm 1904 - Peña Cantero, Álvaro L. (Zenodo, 2021)
Lafoeina longitheca Jäderholm, 1904 (*) Lafoeina longitheca — Peña Cantero, 2009: 1746–1747, fig. 2b–d. Remarks. Peña Cantero (2009) reported this species off Sturge Island, at depths from 96 to 222 m, epibiotic on H. incertus , O. bidentata and Staurotheca compressa Briggs, 1938. : Published as part of Peña Cantero, Álvaro L., 2021, Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica), pp. 321-336 in Zootaxa 4966 (3) on page 325, DOI: 10.11646/zootaxa.4966.3.4, http://zenodo.org/record/4736691 : {"references": ["Jaderholm, E. (1904) Mitteilungen ueber einige von der Schwedischen Antarctic Expedition 1901 - 1903 eingesammelte Hydroiden. Archives de Zoologie Experimentale et Generale, Series 4, 3 (Notes et revue 1), 1 - 14.", "Pena Cantero, A. L. (2009) Benthic hydroids (Cnidaria, Hydrozoa) from the Balleny Islands (Antarctica). Polar Biology, 32, 1743 - 1751. https: // doi. org / 10.1007 / s 00300 - 009 - 0673 - 7", "Briggs, E. A. (1938) Hydroida. Scientific Reports Australasian Antarctic Expedition 1911 - 1914, (C), 9 (4), 1 - 46."]}